lloyd = {

"name": "Lloyd",

"homework": [90.0, 97.0, 75.0, 92.0],

"quizzes": [88.0, 40.0, 94.0],

"tests": [75.0, 90.0]

}

alice = {

"name": "Alice",

"homework": [100.0, 92.0, 98.0, 100.0],

"quizzes": [82.0, 83.0, 91.0],

"tests": [89.0, 97.0]

}

tyler = {

"name": "Tyler",

"homework": [0.0, 87.0, 75.0, 22.0],

"quizzes": [0.0, 75.0, 78.0],

"tests": [100.0, 100.0]

}

student = [lloyd, alice, tyler]

def average(numbers):

total = sum(numbers)

total = float(total)

total = total / len(numbers)

return total

def get_average(student):

homework = (sum(student["homework"])) / 4

quizzes = (sum(student["quizzes"])) /3

tests = (sum(student["tests"])) / 2

soma = (homework * 0.1) + (quizzes * 0.3) + (tests * 0.6)

return soma

def get_letter_grade(score):

if score >= 90:

return "A"

elif score >= 80:

return "B"

elif score >= 70:

return "C"

elif score >= 60:

return "D"

else:

return "F"

def get_class_average(students):

results= []

for student in class:

get_average(student)

results.append(get_average(student))

`return total`

print get_letter_grade(get_average(lloyd))

What is wrong here?

I need to do these steps:

- Set a function called (get_class_average) with an argument (students). you can expect (students) to be a list containing the three students.
- First, create an empty list called (results).
- For each item (student) in the list (class), calculate (get_average (student)) and then call (results.append ()) with this result.
- Finally, return the result of calling (average ()) with (results).

I wrote:

def get_class_average(students):

results= []

for student in class:

get_average(student)

results.append(get_average(student))

`return total`

The console response:

File "python", line 48

for student in class:

^

SyntaxError: invalid syntax